Inorganic-organic multi-shell toughening agent and preparation method thereof

By coating a nano-silica core layer with titanium dioxide, zirconium oxide, polydopamine and methyl ω-undecenoate to form a five-layer core-shell toughening agent, the problems of poor dispersibility and compatibility of existing toughening agents are solved, and the toughness and mechanical properties of thermosetting olefin unsaturated resin materials are improved. It is suitable for fields such as electronics, rail transportation, and aerospace.

CN121293596APending Publication Date: 2026-01-09GUILIN CONINST ELECTRICAL & ELECTRONIC MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511749187.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-26
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

Existing toughening agents have poor dispersibility and compatibility, resulting in insufficient toughness of thermosetting olefin unsaturated resin materials, which affects their application in certain fields.

Method used

An inorganic-organic multi-shell toughening agent is used to form a five-layer core-shell structure by sequentially coating titanium dioxide, zirconium oxide, polydopamine and methyl ω-undecenoate on a nano-silica core layer, thereby enhancing the toughness and compatibility of the material.

Benefits of technology

It significantly improves the toughness, mechanical strength, and overall performance of thermosetting olefin unsaturated resin materials, meeting the high-performance material needs of fields such as electronics, rail transportation, and aerospace.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an inorganic-organic multi-shell toughening agent and a preparation method thereof. According to the toughening agent, nano silicon dioxide serves as a core layer, the surface of the core layer is sequentially coated with titanium dioxide, zirconium oxide, polydopamine and omega-methyl undecylenate to obtain the toughening agent, and the nano silicon dioxide is prepared through an optimized Stober method and is uniform in particle size. According to the toughening agent disclosed by the invention, the inorganic core is coated with the multiple layers of organic shells, so that the problems that a conventional toughening agent is easy to agglomerate, poor in dispersity and poor in compatibility are solved, and meanwhile, adverse effects on the heat resistance and rigidity of a thermosetting olefinic unsaturated resin material are avoided; through strong bonding and crosslinking of organic layer double bonds and resin double bonds, the compatibility and dispersity of the toughening agent and a resin matrix are effectively enhanced, the remarkable toughening effect on a thermosetting olefinic unsaturated resin curing system is achieved from multiple angles, and meanwhile the comprehensive performance such as toughness, mechanical performance, heat resistance and processability of the material is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a toughening agent for use in unsaturated resins, specifically to an inorganic-organic multi-shell toughening agent and its preparation method. Background Technology

[0002] Thermosetting olefin unsaturated resins are a class of thermosetting resins whose molecular chains contain repeating C=C double bonds. Common examples include allyl resins and unsaturated polyester resins. Due to their excellent electrical insulation, dimensional stability, and heat and weather resistance, they are widely used in electronics, rail transportation, aerospace, and other fields. However, thermosetting olefin unsaturated resins also have some significant limitations, with insufficient toughness being a prominent issue. Insufficient toughness makes them prone to brittle fracture under impact or external force, greatly reducing safety and reliability, thus limiting their application in fields requiring high toughness and mechanical strength. To address the problem of insufficient toughness in thermosetting olefin unsaturated resins, a common method is to add toughening agents to the curing system.

[0003] There are many types of toughening agents available, which can be mainly divided into the following three categories:

[0004] Thermoplastic resin toughening agents. For example, the invention patent application with publication number CN119931337A uses homogeneous and heterogeneous thermoplastic resin toughening agents to modify thermosetting resins, thereby improving the toughness and overall mechanical properties of the resin system. However, thermoplastic resin toughening agents typically reduce the heat resistance and rigidity of the material.

[0005] Rubber-based toughening agents. For example, the invention patent application with publication number CN119351023A uses a liquid rubber toughening agent—carboxyl-terminated liquid nitrile butadiene rubber—and a nano-rubber toughening agent—fully vulcanized carboxyl-terminated nitrile butadiene rubber nanoparticles. These can chemically react with epoxy resin to form a "sea-island" structure. Upon impact, the rubber phase can absorb energy, thereby improving the toughness of the epoxy resin material. However, rubber-based toughening agents are often prone to agglomeration and poor dispersibility, resulting in unsatisfactory toughening effects.

[0006] Inorganic nanoparticle toughening agents. For example, the invention patent application with publication number CN120590840A uses modified nano-silica to improve the impact resistance of materials through a microcrack toughening mechanism. Inorganic nanoparticles do not reduce the heat resistance of materials, but they have poor compatibility with resin matrices and are prone to agglomeration, leading to poor dispersion. Surface modification is often required, and they are frequently used in epoxy resin curing systems.

[0007] Therefore, developing a new type of toughening agent to overcome the shortcomings of existing toughening agents, effectively improve the toughness of thermosetting materials, and ensure that other properties are not significantly affected has become a key problem that urgently needs to be solved in this field. Summary of the Invention

[0008] The technical problem to be solved by the present invention is to address the shortcomings of existing toughening agents in terms of poor dispersibility and compatibility, and to provide an inorganic-organic multi-shell toughening agent and its preparation method. This toughening agent is applied to the toughening and curing system of thermosetting olefin unsaturated resin materials, thereby improving the toughness and mechanical strength of thermosetting olefin unsaturated resin materials while enhancing their overall performance.

[0009] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:

[0010] An inorganic-organic multi-shell toughening agent is obtained by sequentially coating titanium dioxide, zirconium oxide, polydopamine, and methyl ω-undecenoate onto the surface of nano-silica as the core layer. The nano-silica is prepared by the following method:

[0011] Take water, anhydrous ethanol and ammonia water and mix them evenly to obtain solution A1;

[0012] Dissolve tetraethyl orthosilicate (TEOS) in anhydrous ethanol to obtain solution A2;

[0013] Solution A1 was stirred at a rate of 1000-1200 r / min. Under this stirring condition, solution A2 was added dropwise to solution A1, with the dropping rate of solution A2 controlled at 2-3 drops / s. After the addition was completed, the stirring rate was adjusted to 360-400 r / min to continue the reaction. After the reaction was completed, the solution was centrifuged, washed, and dried to obtain nano-silica with uniform particle size.

[0014] This invention employs an optimized Stobber method to prepare nano-silica with uniform particle size. Specifically, in an ethanol-ammonia water system of a certain proportion, a TEOS solution is first added dropwise at a specific rate under specific high-speed stirring conditions. After the addition is complete, the stirring rate is adjusted to a specific low rate to control the hydrolysis and condensation reactions of TEOS, thereby obtaining monodisperse nano-silica spheres with uniform particle size. Testing revealed that the obtained nano-silica has a particle size distribution of 400–460 nm, with an average particle size of 420–430 nm.

[0015] Furthermore, during the preparation of nano-silica, the reaction temperature is controlled at 20~30℃, and the reaction continues for 18~24h after the addition is completed to ensure the synthesis of nano-silica and a suitable particle size.

[0016] In a preferred embodiment, the stirring rate is adjusted to 360-400 r / min 1-2 minutes after solution A2 is added dropwise.

[0017] The inorganic-organic multi-shell toughening agent of the present invention has a five-layer core-shell structure, consisting of a core layer (nano-silica layer), a titanium dioxide layer, a zirconium oxide layer, a polydopamine layer, and a methyl ω-undecenoate layer from the inside out. Therefore, the toughening agent described in this application is also referred to as nano-silica@titanium dioxide@zirconia@polydopamine@methyl ω-undecenoate.

[0018] The toughening agent of this invention uses nano-silica as its core, possessing high specific surface area, high strength, and high heat resistance. It provides stable core support for the entire toughening agent and acts as a stress concentration point during the toughening process, absorbing impact energy through a microcrack toughening mechanism. Titanium dioxide is coated on the outer layer of nano-silica, and the two work synergistically to enhance the material's mechanical strength, heat resistance, wear resistance, and UV shielding. The presence of a zirconium oxide layer further increases the material's toughness, rigidity, heat resistance, and wear resistance. Its phase change toughening mechanism allows the material to undergo a phase change when subjected to external force, absorbing energy and preventing crack propagation. Together with the inner nano-silica@titanium dioxide structure, it enhances the overall mechanical properties of the entire structure. The polydopamine layer, with its excellent adhesion, can... The outermost layer of ω-undecenoic acid methyl ester tightly coats the outer layer of zirconium oxide, making the bonding between the layers stronger and forming a strong interaction with the resin matrix, improving the compatibility between the toughening agent and the resin matrix, and enhancing the toughening effect. On the one hand, the outermost layer of ω-undecenoic acid methyl ester undergoes an amidation reaction between the ester group and the amino group of the polydopamine layer, thereby tightly bonding with the inner nano-silica@titanium dioxide@zirconia@polydopamine structure. On the other hand, the double bonds in its molecular structure can undergo a cross-linking reaction with the double bonds in the olefin unsaturated resin, further enhancing the chemical bonding between the toughening agent and the resin matrix, increasing the cross-linking degree of the entire resin curing system, and it itself has good flexibility, which can deform and absorb energy when the material is subjected to impact, thereby effectively improving the toughness of the material.

[0019] Furthermore, the weight ratio of the substances in each layer of the toughening agent from the inside to the outside of the present invention is: silicon dioxide: titanium dioxide: zirconium oxide: polydopamine: ω-undecenoic acid methyl ester = 7~10: 3~6: 5~10: 15~20: 13~18.

[0020] Furthermore, the weight ratio of the substances in each layer of the toughening agent from the inside to the outside of the present invention is: silicon dioxide: titanium dioxide: zirconium oxide: polydopamine: methyl ω-undecenoate = 7~10: 3~5.5: 6~10: 15~18: 13~16.5.

[0021] The preparation method of the above-mentioned inorganic-organic multi-shell toughening agent includes the following steps:

[0022] 1) Preparation of core layer silicon dioxide:

[0023] 1.1) Mix water, anhydrous ethanol, and ammonia thoroughly to obtain solution A1;

[0024] 1.2) Dissolve tetraethyl orthosilicate in anhydrous ethanol to obtain solution A2;

[0025] 1.3) Stir solution A1 at a rate of 1000~1200 r / min. Under this stirring condition, add solution A2 dropwise to solution A1, controlling the dropping rate of solution A2 to be 2~3 drops / s. After the addition is completed, adjust the stirring rate to 360~400 r / min to continue the reaction. After the reaction is completed, centrifuge, wash and dry to obtain nano-silica with uniform particle size.

[0026] 2) Coating the core layer with titanium dioxide to form a titanium dioxide layer, thus obtaining nano-silica@titanium dioxide composite particles;

[0027] 3) A zirconium oxide layer is formed by coating the surface of the titanium dioxide layer, resulting in nano-silica@titanium dioxide@zirconia composite particles;

[0028] 4) Polydopamine is coated onto the surface of the zirconia layer to form a polydopamine layer, thus obtaining nano-silica@titanium dioxide@zirconia@polydopamine composite particles;

[0029] 5) Coating the surface of the dopamine layer with methyl ω-undecenoate to form a methyl ω-undecenoate layer, thus obtaining the inorganic-organic multi-shell toughening agent.

[0030] In preparing the core layer silica, the preferred weight ratio of water, anhydrous ethanol, and ammonia in step 1.1) is 2~2.5:30~35:6~8; the preferred weight ratio of tetraethyl orthosilicate and anhydrous ethanol in step 1.2) is 4~4.5:37~42, and the amount of tetraethyl orthosilicate used in this step is 1.6~2.3 times the weight of water in step 1.1); in step 1.3), the reaction temperature is controlled at 20~30℃, and the reaction continues for 18~24h after the addition is completed to ensure the synthesis and particle size of nano-silica. Preferably, the stirring rate is adjusted to 360~400r / min 1~2min after the addition of solution A2.

[0031] Optionally, in step 2), titanium dioxide is coated onto the surface of the core layer silica using a sol-gel method. Specifically, this includes the following steps:

[0032] 2.1) Disperse nano-silica in anhydrous ethanol to obtain dispersion B1;

[0033] 2.2) Tetraisopropoxide titanium (Ti{OCH(CH3)2}4) and ammonia water were added dropwise to dispersion B1, and the reaction was carried out under stirring.

[0034] 2.3) After the reaction is completed, the reaction product is centrifuged, washed and dried to obtain nano-silica@titanium dioxide composite particles.

[0035] Further, in step 2.1), the weight ratio of nano-silica to anhydrous ethanol is 1:130~150; in step 2.2), the amount of tetraisopropoxide titanium is preferably 1.0~2.8 times the weight of nano-silica in step 2.1), more preferably 1.1~2.0 times; the amount of ammonia is used to control the pH of the system to 8~9.5 (under normal conditions, this pH condition can be achieved when the amount of ammonia is 1.0~1.2 times the weight of tetraisopropoxide titanium), so as to promote the hydrolysis of tetraisopropoxide titanium; the reaction is carried out at 20~30℃, and the reaction time is controlled at 8~12h.

[0036] Optionally, in step 3), zirconium oxide is coated onto the surface of the titanium dioxide layer using a hydrothermal method. Specifically, this includes the following steps:

[0037] 3.1) Disperse nano-silica@titanium dioxide composite particles in water to obtain dispersion C1;

[0038] 3.2) Add zirconium oxychloride octahydrate to dispersion C1, dissolve it, adjust the pH of the system to alkaline, stir the reaction to form a homogeneous zirconium ion precursor solution C2.

[0039] 3.3) Transfer the precursor solution C2 to a polytetrafluoroethylene-lined hydrothermal reactor, seal it, and place it at 160~200℃ for reaction;

[0040] 3.4) After the reaction is complete, the reaction product is cooled and then centrifuged, washed and dried to obtain nano-silica@titanium dioxide@zirconia composite particles.

[0041] Further, in step 3.1), the weight ratio of nano-silica@titanium dioxide composite particles to water is preferably 3:210~240. In step 3.2), the amount of zirconium oxychloride octahydrate used is preferably 1.0~2.6 times the weight of the nano-silica@titanium dioxide composite particles in step 3.1), more preferably 1.5~2.0 times. The pH of the system is adjusted to 8~9 using an alkaline substance such as sodium hydroxide, and a homogeneous zirconium ion precursor solution C2 is formed by stirring the reaction for 20~60 min. The reaction time in step 3.3) is typically controlled to be 10~15 h.

[0042] Optionally, in step 4), polydopamine is coated onto the surface of the zirconia layer using in-situ polymerization. This specifically includes the following steps:

[0043] 4.1) Disperse nano-silica@titanium dioxide@zirconia composite particles in Tris-HCl buffer to obtain dispersion D1;

[0044] 4.2) Add dopamine hydrochloride to dispersion D1, dissolve it, and then stir the reaction under an inert atmosphere.

[0045] 4.3) After the reaction is completed, the reaction product is centrifuged, washed and dried to obtain nano-silica@titanium dioxide@zirconia@polydopamine composite particles.

[0046] Further, in step 4.1), the Tris-HCl buffer solution has a concentration of 0.01 mol / L (used to adjust the pH of the system to 8.5 ± 0.2), and the weight ratio of the nano-silica@titanium dioxide@zirconia composite particles to the Tris-HCl buffer solution is 1:80~90; in step 4.2), the amount of dopamine hydrochloride used is 0.7~1.4 times the weight of the nano-silica@titanium dioxide@zirconia composite particles in step 4.1), more preferably 0.8~1.2 times; the stirring reaction is carried out at 20~30℃ for 20~26 h to ensure dopamine polymerization.

[0047] Optionally, in step 5), methyl ω-undecenoate is coated onto the surface of the polydopamine layer by adding methyl ω-undecenoate and coupling the amino groups on the nano-silica@titanium dioxide@zirconia@polydopamine composite particles to CN. Specifically, this includes the following steps:

[0048] 5.1) Take nano-silica@titanium dioxide@zirconia@polydopamine composite particles and disperse them in anhydrous ethanol to obtain dispersion E1;

[0049] 5.2) Add methyl ω-undecenoate and hydrochloric acid sequentially to dispersion E1 and stir to react;

[0050] 5.3) After the reaction is completed, the reaction product is centrifuged, washed and dried to obtain the inorganic-organic multi-shell toughening agent (nano silica@titanium dioxide@zirconia@polydopamine@methyl ω-undecenoate) of the present invention.

[0051] Further, in step 5.1), the weight ratio of nano-silica@titanium dioxide@zirconia@polydopamine composite particles to anhydrous ethanol is 1:60~70; in step 5.2), the amount of ω-undecenoic acid methyl ester is 0.3~0.6 times, more preferably 0.3~0.5 times, of the weight of the nano-silica@titanium dioxide@zirconia@polydopamine composite particles in step 5.1); when the hydrochloric acid is concentrated hydrochloric acid, the amount of hydrochloric acid is 0.4~0.6 times, more preferably 0.5 times, of the weight of ω-undecenoic acid methyl ester; the stirring reaction is carried out at 50~80℃ for 5~8h to ensure that the ester groups of ω-undecenoic acid methyl ester undergo amidation reaction with the amino groups on the surface of polydopamine to form the final coating layer.

[0052] The toughening agent prepared by the above method has the following weight ratio of substances in each layer from the inside to the outside: silicon dioxide: titanium dioxide: zirconium oxide: polydopamine: ω-undecenoic acid methyl ester = 7~10: 3~6: 5~10: 15~20: 13~18, and further within the range of 7~10: 3~5.5: 6~10: 15~18: 13~16.5.

[0053] In this application, the water is deionized water, and the ammonia water refers to ammonia water with a concentration of 25-28% by mass.

[0054] This application further includes the application of the aforementioned inorganic-organic multi-shell toughening agent in the preparation of thermosetting olefin unsaturated resin molding compounds. Further, it includes the application as a toughening agent in the preparation of thermosetting olefin unsaturated resin molding compounds.

[0055] Compared with the prior art, the present invention is characterized by:

[0056] 1. By coating the inorganic core with a multi-layered organic shell, the problems of easy agglomeration, poor dispersibility and poor compatibility of conventional toughening agents are overcome, while avoiding the adverse effects on the heat resistance and rigidity of thermosetting olefin unsaturated resin materials.

[0057] 2. Through strong cross-linking between the double bonds of the organic layer and the double bonds of the resin, the compatibility and dispersibility of the toughening agent and the resin matrix are effectively enhanced. Furthermore, through the synergistic effect of the various layers of nano-silica@titanium dioxide@zirconia@polydopamine@ω-undecenoic acid methyl ester, a significant toughening effect is achieved on the thermosetting olefin unsaturated resin curing system from multiple perspectives. At the same time, the comprehensive properties of the material, such as toughness, mechanical properties, heat resistance, and processability, are also enhanced.

[0058] 3. The thermosetting olefinic unsaturated resin materials toughened with the toughening agent described in this invention achieve comprehensive optimization of their overall performance while maintaining their original excellent properties, better meeting the demands for high-performance materials in fields such as electronics, electrical engineering, rail transportation, and aerospace. Experimental results show that, compared to samples without toughening agent, injection molded samples of allyl resin and / or unsaturated polyester resin molding compounds toughened with the toughening agent described in this invention exhibit ≥35.6% higher undamaged impact strength, ≥33.3% higher notched impact strength, ≥29.3% higher flexural strength, and ≥8.9% higher load deformation temperature. Detailed Implementation

[0059] To better explain the technical solution of the present invention, the present invention will be further described in detail below with reference to the embodiments, but the implementation of the present invention is not limited thereto.

[0060] All quantities mentioned in the following embodiments are by weight.

[0061] Example 1: Preparation of Inorganic-Organic Multi-Shell Toughening Agent

[0062] 1) Preparation of core layer silicon dioxide:

[0063] 1.1) Take 2.23 parts of deionized water, 32 parts of anhydrous ethanol and 7 parts of ammonia water, place them in a round-bottom flask, and stir for 30 min at 25℃ and 500 r / min to obtain solution A1;

[0064] 1.2) Take 4.37 parts of tetraethyl orthosilicate and 40 parts of anhydrous ethanol, place them in a beaker, and stir for 30 min at 25℃ and 500 r / min to obtain solution A2;

[0065] 1.3) Stir solution A1 at a rate of 1100 r / min, transfer solution A2 to a constant pressure dropping funnel, and add it to solution A1 at a dropping rate of 2 drops / s. After 1 min of dropping, adjust the stirring rate to 380 r / min and continue stirring at 25℃ for 20 h.

[0066] 1.4) After the reaction was completed, the resulting reaction product was transferred to a centrifuge tube and centrifuged at 8000 r / min for 15 min. The precipitate was collected and washed three times with anhydrous ethanol. The washed precipitate was then dried in a vacuum drying oven at 60℃ and -0.09 MPa for 8 h to obtain nano-silica spheres. The particle size distribution of the obtained nano-silica spheres was found to be 420–440 nm, with an average particle size of 425 nm.

[0067] 2) Preparation of the first coating layer – nano-silica@titanium dioxide composite particles:

[0068] 2.1) Take 2 parts of the nano-silica prepared in step 1) and 280 parts of anhydrous ethanol and place them in a beaker. Disperse them by ultrasonication at room temperature for 30 min to obtain dispersion B1.

[0069] 2.2) Add 3.55 parts of tetraisopropoxide and 3.9 parts of ammonia water dropwise to dispersion B1. After the addition is complete, place the reaction solution at 25℃ and 500r / min and stir for 10h.

[0070] 2.3) After the reaction was completed, the resulting reaction product was transferred to a centrifuge tube and centrifuged at 8000 r / min for 15 min. The precipitate was collected, washed three times with anhydrous ethanol, and then washed once with deionized water. The washed precipitate was placed in a vacuum drying oven at 60℃ and -0.09 MPa and dried for 8 h to obtain nano-silica@titanium dioxide composite particles.

[0071] 3) Preparation of the second coating layer – nano-silica@titanium dioxide@zirconia composite particles:

[0072] 3.1) Take 3 portions of the nano-silica@titanium dioxide composite particles prepared in step 2) and 225 portions of deionized water and place them in a beaker. Disperse them ultrasonically at room temperature for 20 min to obtain dispersion C1.

[0073] 3.2) Add 5.2 parts of zirconium oxychloride octahydrate to dispersion C1, stir and dissolve at 25℃ and 400 r / min, adjust the pH to 8.5 with 1 mol / L sodium hydroxide solution, and continue stirring for 30 min to form a homogeneous zirconium ion precursor solution C2.

[0074] 3.3) Transfer the precursor solution C2 to a 500 mL polytetrafluoroethylene-lined hydrothermal reactor, seal it, place it in an oven, heat it to 180 °C, and keep it at that temperature for 12 h.

[0075] 3.4) After the reaction is complete, the product is naturally cooled to room temperature. The reaction product is transferred to a centrifuge tube and centrifuged at 8000 r / min for 15 min. The precipitate is collected, washed three times with deionized water, and then washed once with anhydrous ethanol. The washed precipitate is placed in a vacuum drying oven at 60℃ and -0.09 MPa and dried for 8 h to obtain nano-silica@titanium dioxide@zirconia composite particles.

[0076] 4) Preparation of the third-layer coating – nano-silica@titanium dioxide@zirconia@polydopamine composite particles:

[0077] 4.1) Take 5 parts of the nano-silica@titanium dioxide@zirconia composite particles prepared in step 3) and 420 parts of Tris-HCl buffer solution (concentration 0.01mol / L) and place them in a container. Disperse them ultrasonically at room temperature for 25 min to form a stable dispersion D1 (at this time, the pH of the system is 8.5).

[0078] 4.2) Add 5 parts of dopamine hydrochloride to dispersion D1, stir to dissolve, then purge with nitrogen for 30 min to remove oxygen from the system, and then continue stirring and reacting for 24 h under nitrogen protection, 25 °C and 400 r / min.

[0079] 4.3) After the reaction is complete, the reaction product is transferred to a centrifuge tube and centrifuged at 8000 r / min for 20 min. The precipitate is collected and washed repeatedly with deionized water until the supernatant is colorless and transparent. The washed precipitate is placed in a vacuum drying oven at 50℃ and -0.09 MPa for 10 h to obtain nano-silica@titanium dioxide@zirconia@polydopamine composite particles.

[0080] 5) Preparation of composite particles coated with a fourth shell – nano-silica@titanium dioxide@zirconia@polydopamine@ω-undecenoate (coupling modification):

[0081] 5.1) Take 5.14 parts of the nano-silica@titanium dioxide@zirconia@polydopamine composite particles prepared in step 4) and 330 parts of anhydrous ethanol and place them in a container. Disperse them ultrasonically at room temperature for 20 min to obtain dispersion E1.

[0082] 5.2) Add 2 parts of ω-undecenoic acid methyl ester and 1 part of concentrated hydrochloric acid (catalytic effect) to dispersion E1 in sequence, and stir the reaction at 60℃ and 500r / min for 6h to allow the ester group of ω-undecenoic acid methyl ester to undergo an amidation reaction with the amino group on the surface of polydopamine to form the final coating layer.

[0083] 5.3) After the reaction is complete, the resulting reaction solution is transferred to a centrifuge tube and centrifuged at 8000 r / min for 15 min. The precipitate is collected, washed three times with anhydrous ethanol, and the washed precipitate is dried in a vacuum drying oven at 50℃ and -0.09 MPa for 8 h to obtain nano-silica@titanium dioxide@zirconia@polydopamine@ω-undecenoic acid methyl ester, which is the inorganic-organic multi-shell toughening agent of the present invention.

[0084] Upon testing, the weight ratio of the substances in each layer of the toughening agent obtained in this example from the inside out was: silicon dioxide: titanium dioxide: zirconium oxide: polydopamine: ω-undecenoic acid methyl ester = 8:4:8:16:14.

[0085] Comparative Example 1-1

[0086] Repeat Example 1, except that in step 1), commercially available nano-silica with an average particle size of 425 nm is used directly as the core layer silica.

[0087] According to the test, the weight ratio of the substances in each layer of the toughening agent obtained in this example from the inside to the outside is: silicon dioxide: titanium dioxide: zirconium oxide: polydopamine: methyl ω-undecenoate = 8: 2.7: 5: 11: 9.

[0088] Comparative Examples 1-2

[0089] Repeat Example 1, except that in step 1.3), after 1 minute of dripping, the stirring rate of 1100 r / min is maintained and stirring is continued at 25°C for 20 hours, while the rest remains unchanged.

[0090] Testing revealed that the particle size distribution of the nano-silica spheres prepared in this example ranged from 120 to 300 nm, with an average particle size of 210 nm. The weight ratio of the substances in each layer of the toughening agent prepared in this example, from the inside out, was: silica:titanium dioxide:zirconia:polydopamine:methyl ω-undecenoate = 8:5:10:17.5:16.

[0091] Comparative Examples 1-3

[0092] Repeat Example 1, except that in step 1.3), the stirring rate is controlled at 400 r / min before and after adding solution A2, while the rest remains unchanged.

[0093] Testing revealed that the particle size distribution of the nano-silica spheres prepared in this example ranged from 500 to 620 nm, with an average particle size of 560 nm. The weight ratio of the substances in each layer of the toughening agent prepared in this example, from the inside out, was: silica:titanium dioxide:zirconia:polydopamine:methyl ω-undecenoate = 8:3:6:13:11.

[0094] Example 2: Toughening allyl molding compound with the inorganic-organic multi-shell toughening agent of the present invention

[0095] I. Formula

[0096] Eight parts of toughening agent, the inorganic-organic multi-shell toughening agent prepared in Example 1 was selected;

[0097] 30 parts of solid allyl resin, selected from solid diallyl isophthalate resin;

[0098] 30 parts of reinforcing fiber, selected from glass fibers with a diameter of 10~13μm and a length of 3~6mm;

[0099] 30 parts of filler, selected from magnesium hydroxide and aluminum hydroxide (weight ratio 1:1).

[0100] One part of curing agent, using dicumyl peroxide;

[0101] One part of release agent, preferably zinc stearate.

[0102] II. Preparation Method

[0103] Weigh each component according to the above formula, put them into a high-speed mixer, mix them evenly, and then plasticize them through a twin-screw extruder. The temperature of each section of the twin-screw extruder is controlled at 85±5℃. The extruded material is fed into a single-screw granulator for granulation. The temperature of each section of the single-screw granulator is controlled at 95±5℃ to obtain regular or irregular granulated allyl molding compound, which is then injection molded into samples for performance testing.

[0104] Comparative Example 2-1

[0105] Example 2 was repeated, except that the same amount of commercially available nano-silica toughening agent was used instead of the inorganic-organic multi-shell toughening agent prepared in Example 1.

[0106] Comparative Example 2-2

[0107] Example 2 was repeated, except that the same amount of commercially available methyl ω-undecenoate was used instead of the inorganic-organic multi-shell toughening agent prepared in Example 1.

[0108] Comparative Examples 2-3

[0109] Example 2 was repeated, except that no toughening agent was used.

[0110] Comparative Examples 2-4

[0111] Example 2 was repeated, except that the toughening agent prepared in Comparative Example 1-1 was used in the same amount instead of the inorganic-organic multi-shell toughening agent prepared in Example 1.

[0112] Comparative Examples 2-5

[0113] Example 2 was repeated, except that the toughening agent prepared in the same amount as that in Comparative Examples 1-2 was used instead of the inorganic-organic multi-shell toughening agent prepared in Example 1.

[0114] Comparative Examples 2-6

[0115] Example 2 was repeated, except that the toughening agent prepared in Comparative Examples 1-3 was used instead of the inorganic-organic multi-shell toughening agent prepared in Example 1, with the same amount of the toughening agent.

[0116] Example 3: Preparation of unsaturated polyester molding compound toughened with inorganic-organic multi-shell toughening agent

[0117] I. Formula

[0118] Six parts of toughening agent, the inorganic-organic multi-shell toughening agent prepared in Example 1 was selected;

[0119] 32 parts of solid unsaturated polyester resin, selected as phthalic dry unsaturated polyester resin;

[0120] 30 parts of reinforcing fiber, selected from glass fibers with a diameter of 10~13μm and a length of 3~6mm;

[0121] 30 parts of filler, selected from magnesium hydroxide and aluminum hydroxide (weight ratio 1:1).

[0122] One part of curing agent, using dicumyl peroxide;

[0123] One part of release agent, preferably zinc stearate.

[0124] II. Preparation Method

[0125] Weigh each component according to the above formula, put them into a high-speed mixer, mix them evenly, and then plasticize them through a twin-screw extruder. The temperature of each section of the twin-screw extruder is controlled at 65±5℃. The extruded material is fed into a single-screw granulator for granulation. The temperature of each section of the single-screw granulator is controlled at 95±5℃. Regular or irregular granules of unsaturated polyester resin molding compound are obtained and injection molded into samples for performance testing.

[0126] Comparative Example 3-1

[0127] Example 3 was repeated, except that no toughening agent was used.

[0128] Comparative Example 3-2

[0129] Repeat Example 3, except that the toughening agent prepared in Comparative Example 1-1 was used in the same amount instead of the inorganic-organic multi-shell toughening agent prepared in Example 1.

[0130] Example 4: Preparation of Inorganic-Organic Multi-Shell Toughening Agent

[0131] Repeat Example 1, except that step 1.3) is performed as follows:

[0132] 1.3) Stir solution A1 at a rate of 1000 r / min. Transfer solution A2 to a constant pressure dropping funnel and add it to solution A1 at a dropping rate of 3 drops / s. After 2 minutes of dropping, adjust the stirring rate to 360 r / min and continue stirring at 25°C for 24 hours.

[0133] Testing revealed that the particle size distribution of the nano-silica spheres prepared in this example ranged from 420 to 460 nm, with an average particle size of 430 nm.

[0134] Example 5: Preparation of Inorganic-Organic Multi-Shell Toughening Agent

[0135] Repeat Example 1, except that step 1.3) is performed as follows:

[0136] 1.3) Stir solution A1 at a rate of 1200 r / min. Transfer solution A2 to a constant pressure dropping funnel and add it to solution A1 at a dropping rate of 3 drops / s. After 2 minutes of dropping, adjust the stirring rate to 400 r / min and continue stirring at 20°C for 18 hours.

[0137] Testing revealed that the particle size distribution of the nano-silica spheres prepared in this example ranged from 400 to 440 nm, with an average particle size of 420 nm.

[0138] Example 6: Toughening allyl molding compound with the inorganic-organic multi-shell toughening agent of the present invention

[0139] Example 2 was repeated, except that the toughening agent prepared in Example 4 was used instead of the inorganic-organic multi-shell toughening agent prepared in Example 1 in the same amount.

[0140] Example 7: Toughening allyl molding compound with the inorganic-organic multi-shell toughening agent of the present invention

[0141] Example 2 was repeated, except that the toughening agent prepared in Example 5 was used instead of the inorganic-organic multi-shell toughening agent prepared in Example 1 in the same amount.

[0142] The undamaged impact strength, notched impact strength, flexural strength, and load deformation temperature of the molding compound injection samples prepared in Examples 2, 3, 6, and 7, as well as Comparative Examples 2-1 to 2-6, and Comparative Examples 3-1 to 3-2, were tested according to relevant national industry standards. The results are shown in Table 1 below.

[0143] Table 1:

[0144]

[0145] As shown in Table 1, compared with the molding compound injection samples without any toughening agent, the molding compound injection samples toughened with commercially available nano silica toughening agent and ω-undecenoic acid methyl ester showed only a slight increase in unblemished impact strength, notched impact strength, and flexural strength; while the molding compound injection samples toughened with the inorganic-organic multi-shell toughening agent prepared in this invention showed a significant increase in unblemished impact strength, notched impact strength, and flexural strength, and the load deformation temperature was also increased at the same time.

[0146] The inorganic-organic multi-shell toughening agent nano-silica@titanium dioxide@zirconia@polydopamine@methyl ω-undecenoate specially prepared in this invention can toughen thermosetting olefinic unsaturated resin materials. While maintaining the original excellent electrical insulation, dimensional stability and heat resistance of the materials, it can improve the toughness and mechanical strength of the materials, and at the same time improve their comprehensive performance, so as to better meet the needs of high-performance materials in the fields of electronics, electrical engineering, rail transportation, aerospace and other fields.

[0147] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. An inorganic-organic multi-shell toughening agent, characterized in that, It is obtained by sequentially coating titanium dioxide, zirconium oxide, polydopamine, and methyl ω-undecenoate onto the surface of nano-silica as the core layer. The nano-silica is prepared by the following method: Take water, anhydrous ethanol and ammonia water and mix them evenly to obtain solution A1; Dissolve tetraethyl orthosilicate in anhydrous ethanol to obtain solution A2; Solution A1 was stirred at a rate of 1000-1200 r / min. Under this stirring condition, solution A2 was added dropwise to solution A1, with the dropping rate of solution A2 controlled at 2-3 drops / s. After the addition was completed, the stirring rate was adjusted to 360-400 r / min to continue the reaction. After the reaction was completed, the solution was centrifuged, washed, and dried to obtain nano-silica with uniform particle size.

2. The inorganic-organic multi-shell toughening agent according to claim 1, characterized in that, The weight ratio of the substances in each layer of the toughening agent from the inside to the outside is: silicon dioxide: titanium dioxide: zirconium oxide: polydopamine: methyl ω-undecenoate = 7~10: 3~6: 5~10: 15~20: 13~18.

3. The inorganic-organic multi-shell toughening agent according to claim 1, characterized in that, The weight ratio of the substances in each layer of the toughening agent from the inside to the outside is: silicon dioxide: titanium dioxide: zirconium oxide: polydopamine: methyl ω-undecenoate = 7~10: 3~5.5: 6~10: 15~18: 13~16.

5.

4. The preparation method of the inorganic-organic multi-shell toughening agent according to claim 1, comprising the following steps: 1) Preparation of core layer silicon dioxide: 1.1) Mix water, anhydrous ethanol, and ammonia thoroughly to obtain solution A1; 1.2) Dissolve tetraethyl orthosilicate in anhydrous ethanol to obtain solution A2; 1.3) Stir solution A1 at a rate of 1000~1200 r / min. Under this stirring condition, add solution A2 dropwise to solution A1, controlling the dropping rate of solution A2 to be 2~3 drops / s. After the addition is completed, adjust the stirring rate to 360~400 r / min and continue the reaction. After the reaction is completed, centrifuge, wash and dry to obtain nano-silica with uniform particle size. 2) Coating the core layer with titanium dioxide to form a titanium dioxide layer, thus obtaining nano-silica@titanium dioxide composite particles; 3) A zirconium oxide layer is formed by coating the surface of the titanium dioxide layer, resulting in nano-silica@titanium dioxide@zirconia composite particles; 4) Polydopamine is coated onto the surface of the zirconia layer to form a polydopamine layer, thus obtaining nano-silica@titanium dioxide@zirconia@polydopamine composite particles; 5) Coating the surface of the dopamine layer with methyl ω-undecenoate to form a methyl ω-undecenoate layer, thus obtaining the inorganic-organic multi-shell toughening agent.

5. The preparation method according to claim 4, characterized in that, In step 2), titanium dioxide is coated onto the surface of the core layer silica using the sol-gel method.

6. The preparation method according to claim 4, characterized in that, In step 3), zirconium oxide is coated onto the surface of the titanium dioxide layer using a hydrothermal method.

7. The preparation method according to claim 4, characterized in that, In step 4), polydopamine is coated onto the surface of the zirconia layer using in-situ polymerization.

8. The preparation method according to any one of claims 4 to 7, characterized in that, The weight ratio of the substances in each layer of the toughening agent from the inside to the outside is: silicon dioxide: titanium dioxide: zirconium oxide: polydopamine: methyl ω-undecenoate = 7~10: 3~6: 5~10: 15~20: 13~18.

9. The preparation method according to any one of claims 4 to 7, characterized in that, The weight ratio of the substances in each layer of the toughening agent from the inside to the outside is: silicon dioxide: titanium dioxide: zirconium oxide: polydopamine: methyl ω-undecenoate = 7~10: 3~5.5: 6~10: 15~18: 13~16.

5.

10. The use of the inorganic-organic multi-shell toughening agent according to any one of claims 1 to 3 in the preparation of thermosetting olefinic unsaturated resin molding compounds.

Citation Information

Patent Citations

  • Epoxy resin binder as well as preparation method and application thereof

    CN119351023A

  • Preparation method of homogeneous and heterogeneous toughened thermosetting resin

    CN119931337A

  • Epoxy resin composite coating and preparation method thereof

    CN120590840A